Literary memory and political violence: trauma narratives in Indonesian historical fiction - Kadek Nara Widyatnyana (Indonesian Journal of Politics and Literary Studies, 2026)
Background: Political violence in Indonesian history, especially colonial repression and the 1965 mass violence, has produced enduring trauma often absent from official historiography. Objective: This study examines how Indonesian historical fiction constructs literary memory and represents political violence through discourse and narrative form. Method: A qualitative interpretive approach integrates Critical Discourse Analysis, narrative analysis, and trauma-oriented literary analysis of selected novels. Results: Violence is represented through indirection—euphemism, silence, and abstraction—while trauma appears in non-linear, repetitive, and fragmented narratives; metaphor and restrained diction mediate unspeakable experiences. Implication: These findings position historical fiction as a counter-archive that ethically represents trauma and expands discourse on memory and post-authoritarian literature. Novelty: This study integrates discourse, narrative, and trauma analysis to reveal how linguistic and aesthetic strategies function as ethical mechanisms of witnessing political violence.